READING COMPETENCE AND ENGAGEMENT OF LATVIAN STUDENTS IN THE VIEW OF OECD PISA 2018 RESULTS - Kangro, Ilze; Kangro, Andris; Kiseļova, Rita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Students' reading competence determines the achievements of learners in all areas of school education as well as in their further education, professional activity and life. The results of the OECD Program for International Student Assessment - OECD PISA 2018 confirm the need to improve reading competence in Latvia (OECD, 2019).The aim of the study is to analyze the achievement of Latvia's fifteen-year-old students in OECD PISA 2018 and the previous international program cycles in relation to students' reading engagement and its changes. Reading engagement significantly influences not only students' reading competence but are in themselves one of the goals of modern education (Guthrie & Wigfield, 2000; Guthrie, Klauda & Ho, 2013). The study will use the OECD PISA international databases for statistical analysis the data of Latvia and other countries for comparisons with OECD averages, and especially with the attitudes and achievements of Estonian and Finnish students. The analysis of the first results shows that the promotion of reading engagement among Latvian students, especially boys, is one of the factors for increasing reading competence.